Effects of Compression Garments on Muscle Strength and Power Recovery Post-Exercise: A Systematic Review and Meta-Analysis - Xiang Li; Hao Su; Liwen Du; Gen Li; Yuanyuan Lv; Xiaojie Liu; Lin Feng; Laikang Yu (Life)
This study investigated the effects of compression garments on mitigating the decline in muscle strength and power resulting from exercise-induced muscle fatigue. Searches were performed in PubMed, Web of Science, EBSCO, Cochrane, and Scopus databases. The three-level restricted maximum likelihood random effects model was used to synthesize the data. Twenty-seven studies met the inclusion criteria. Compression garments had significant restorative effects on muscle strength (Hedges’s g = −0.21, p < 0.01) and power (Hedges’s g = −0.23, p < 0.01) after exercise-induced muscle fatigue. Subgroup analysis revealed that compression garments were effective in mitigating the decline in muscle strength when the rest intervals were 1–48 h and over 72 h and in mitigating the decline in power when the resting interval was 1–24 h. In addition, compression garments significantly mitigated the decline in muscle strength, during rest intervals of 1–24 h for trained individuals and over 72 h for both trained and untrained individuals, after exercise-induced muscle fatigue. In conclusion, compression garments significantly mitigated the decline in muscle strength after exercise-induced muscle fatigue. Both trained and untrained individuals could benefit from compression garments, with the effectiveness of compression garments being more pronounced in trained individuals compared to untrained ones.